Intelligent assisted living in pregnancy - Zaman, S. M. Tanveer; Tasneem, Rafia; Shakerin, Tasmia (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.